2021
DOI: 10.1021/acs.jpcc.1c05148
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Fe Activating One-Dimensional α-Ni(OH)2 Nanobelts for Efficient Oxygen Evolution Reaction

Abstract: Development of high-efficiency and inexpensive oxygen evolution reaction (OER) catalysts is highly desirable for water electrolysis devices and rechargeable metal–air batteries. Herein, we report novel one-dimensional (1D) Fe-doped α-Ni­(OH)2 nanobelts as OER-active electrocatalysts. In-depth characterizations revealed that Fe atoms are incorporated into the lattice of Ni­(OH)2, resulting in the strong electron interaction with active Ni sites. Moreover, a contraction of Ni–O bond distance induced by Fe is rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…32,33 Second, the electron interaction between Ni and Fe was proved to adjust the intermediate adsorption energy. 40 Finally, multivalence Ni and Fe ions could provide continuous and fast electron transfer paths. 35 However, when Fe doping amount keeps on increasing from 10% to 20%, the OER activity of 0.2 Fe-NiS/MoS 2 decreases.…”
Section: Pccp Papermentioning
confidence: 99%
“…32,33 Second, the electron interaction between Ni and Fe was proved to adjust the intermediate adsorption energy. 40 Finally, multivalence Ni and Fe ions could provide continuous and fast electron transfer paths. 35 However, when Fe doping amount keeps on increasing from 10% to 20%, the OER activity of 0.2 Fe-NiS/MoS 2 decreases.…”
Section: Pccp Papermentioning
confidence: 99%
“…). , Among numerous vanadium oxides, VO 2 (A) is the most promising material for energy storage and conversion which is due to the highest oxidation state of vanadium, enabling to store more electrons with the highest stability toward H 2 and O 2 production. , Moreover, VO 2 (A) acts as a precursor material for the transformation of other VO 2 polymorphs. , Thus, the unceasing approach to produce H 2 and O 2 can possibly solve the problem of energy crisis. Moreover, recent studies showed that the electrocatalytic activities of any monometallic electrocatalyst can be improved by the incorporation of any secondary elements such as Mn, Co, Fe, and so on as alloys, core shells, and so on. Many efforts have been made for the synthesis of bimetallic-based electrocatalysts for overall water splitting. , Accordingly, the overall electrocatalytic process could be enhanced with the presence of multiple valence ions in the electrocatalyst. , …”
Section: Introductionmentioning
confidence: 99%
“…However, the OER performance of these catalysts is still unsatisfactory due to their poor stability in alkaline electrolytes, which hinder their applications for OWS. On the contrary, transition-metal oxides , and hydroxides, , especially Fe-based layered double hydroxides (LDHs), have been regarded as efficient catalysts for OER under an alkaline environment due to the strong synergistic effect attributed to the incorporation of Fe and tunable electronic, catalytic, and electrochemical properties. These aspectes can effectively promote the absorption and dissociation of hydroxyl species. , For example, Peng et al designed a cation-vacancy-decorated NiFe-LDH catalyst with high efficiency and stability in OER .…”
Section: Introductionmentioning
confidence: 99%